2021
DOI: 10.3390/brainsci11060690
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity Analysis of Brain Activated Regions during Distracted Driving

Abstract: This study aims to use functional magnetic resonance imaging (fMRI) to assess the effective connectivity between the regions of the brain activated when driving and performing a secondary task (addition task). The subjects used an MR-compatible driving simulator ㅊ to manipulate the driving wheel with both hands and control the pedals (accelerator and brake) with their right foot as if they were driving in an actual environment. Effective connectivity analysis was performed for three regions of the right and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Among them, the subjective detection method is affected by the subjective judgment ability of the driver and the researcher, and has certain limitations in detecting the fatigue state, and is usually used as an auxiliary method. In recent years, people have conducted a lot of research on objective methods of driving fatigue detection (Jiao et al 2004, Dorrian et al 2007, Liu et al 2017, Choi et al 2021. Studies have shown that using physiological signal as the index to evaluate driving fatigue has the advantages of objectivity and accuracy, convenient collection and good universality, which is a promising method to study driving fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the subjective detection method is affected by the subjective judgment ability of the driver and the researcher, and has certain limitations in detecting the fatigue state, and is usually used as an auxiliary method. In recent years, people have conducted a lot of research on objective methods of driving fatigue detection (Jiao et al 2004, Dorrian et al 2007, Liu et al 2017, Choi et al 2021. Studies have shown that using physiological signal as the index to evaluate driving fatigue has the advantages of objectivity and accuracy, convenient collection and good universality, which is a promising method to study driving fatigue.…”
Section: Introductionmentioning
confidence: 99%